2013
DOI: 10.1109/tasc.2012.2236603
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Properties of Superconducting Atomic-Layer Deposited TiN Films

Abstract: Abstract-We have grown superconducting TiN films by atomic layer deposition with thicknesses ranging from 6 to 89 nm. This deposition method allows us to tune the resistivity and critical temperature by controlling the film thickness. The microwave properties are measured, using a coplanar-waveguide resonator, and we find internal quality factors above a million, high sheet inductances (5.2-620 pH), and pulse response times up to 100 µs. The high normal state resistivity of the films (> 100 µΩcm) affects the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 20 publications
6
41
0
Order By: Relevance
“…Moreover, a systematic study of the electrodynamic response of the microwave resonators showed that the behavior of TiN films deviates from conventional Mattis-Bardeen theory and from the behavior of conventional superconductors such as aluminum [14]. The temperature dependence of the relaxation time, presumably the quasiparticle lifetime, probed in superconducting microwave resonators of TiN films is found to be much weaker than the exponential predicted dependence in Kaplan theory [15]. In addition for TiN MKIDs it was observed that the dissipative response has a shorter decay time I than the non-dissipative response at ultralow temperatures [8].…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, a systematic study of the electrodynamic response of the microwave resonators showed that the behavior of TiN films deviates from conventional Mattis-Bardeen theory and from the behavior of conventional superconductors such as aluminum [14]. The temperature dependence of the relaxation time, presumably the quasiparticle lifetime, probed in superconducting microwave resonators of TiN films is found to be much weaker than the exponential predicted dependence in Kaplan theory [15]. In addition for TiN MKIDs it was observed that the dissipative response has a shorter decay time I than the non-dissipative response at ultralow temperatures [8].…”
mentioning
confidence: 83%
“…The average growth rate of the TiN film is 0.45 Å per cycle. The details of this technique are described in [15].…”
Section: Phonon Timementioning
confidence: 99%
See 1 more Smart Citation
“…Several ALD TiN films have been deposited on high resistivity (> 10 kΩcm) Si (100) substrates covered with a thin surface layer of native silicon oxide (for details see Coumou et al [17]). The microwave properties of these TiN films have been analysed in detail by Driessen et al [18] and by Coumou et al [19].…”
mentioning
confidence: 99%
“…Reported results were obtained both with sputtered TiN films and with films made by an ALD process [8, 12]. Study of electrodynamic response shows that the behaviour of TiN films deviates from Mattis–Bardeen theory [10] and temperature dependence of microwave-probed relaxation time has weaker temperature dependence than predicted in Kaplan theory [9]. At the same time, relaxation times measured in both sputtered and ALD TiN films are close to show similar values and temperature dependencies [13, 14].…”
Section: Introductionmentioning
confidence: 99%